PROBLEMS IN REGULATING CHILD NEGLECT: REGULATORY LIMITATIONS IN INDONESIA - M. Tantowi Nur Ansori; Made Warka (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The issue of child abandonment in Indonesian marriage law has significant implications for legal certainty and the protection of children's rights. Law Number 1 of 1974 concerning Marriage (as amended by Law No. 16/2019) regulates the status of legitimate and illegitimate children through the provisions of Articles 42, 43, and 44, while the Compilation of Islamic Law views marriage as a contract that creates a legal relationship and parental obligations towards children. Constitutional Court Decision Number 46/PUU-VIII/2010 expanded access to proof of kinship by including scientific and technological evidence. However, the practice of abandonment—including cases that have attracted public attention—demonstrates gaps in the evidentiary system, the risk of subordination of children's rights, and the impact on children's inheritance rights and social status. This study uses a normative juridical approach and case studies to analyze regulations, judicial decisions, and the implications of the practice of abandonment for children's interests. The results of the study indicate: (1) a misalignment between formal legal provisions and evidentiary mechanisms in practice; (2) The Constitutional Court's decision opens up opportunities for rights restoration through scientific evidence, but its implementation is still hampered by access and understanding by relevant parties; and (3) child protection requires more responsive legal mechanisms and supporting policies to ensure legal certainty and the fulfillment of children's rights. It is recommended to strengthen procedures for proving kinship, educate the public about the law, and improve access to forensic/medical services to support fair court decisions that support the best interests of children.